Health‑Related quality of life of patients on antiretroviral therapy at the Federal Medical Center, Makurdi, Nigeria (2019)
Context: Health related quality of life (HRQL) indices could provide information about the effects of disease progression and the effectiveness of medical interventions that cannot be obtained using objective clinical measures. Aim: The aim of this study is to assess HRQL of patients on highly active antiretroviral therapy (HAART) at the Federal Medical Center, Makurdi in North Central Nigeria. Settings and Design: The study was a cross‑sectional survey among people living with HIV/AIDs (PLWHAs) on HAART. Methods: The 546 PLWHAs on HAART were selected using systematic sampling technique. A modification of the 36‑Item Short‑Form Health Survey Version 2 questionnaire was used to assess respondents’ HRQL in eight dimensions: Physical functioning (PF), role‑physical (RP), role‑emotional (RE), social functioning (SF), bodily pain (BP), vitality (VT), mental health (MH), and general health (GH). Data generated after measuring and scoring HRQL using standard methods were analyzed using the SPSS 17. Results: Good HRQL ratings included: PF (98.9%), RE (98.7%), SF (98.2%), VT (96.9%), RP (96.5%), MH (96.3%), BP (94.1%), and GH (93.4%). Predictors of good HRQL were as follows: Age <40 years (odds ratio [OR] = 4.26, confidence interval [CI] = 1.49–12.11) and being currently employed (OR = 3.20, CI = 1.08–9.49) (RP); and having a caregiver (OR = 4.94, CI = 1.33–18.27). Predictors of less likelihood of good HRQL were: Enjoying social support (OR = 0.12, CI = 0.03–0.55) (RP; MH); being without spouse/partner (OR = 0.43, CI = 0.21–0.91) (GH). Conclusions: HAART improves HRQL of HIV patients. Clinicians need to be responsive to factors related to disclosure, having a caregiver, and social support as a means of improving HRQL.